The Use of PT Petro Kimia’s by-Product Gypsum as Fill Materials - Raditya Widiatama; Indrasurya Budisatria Mochtar; Noor Endah Mochtar (IPTEK Journal of Proceedings Series, 2020)
Gypsum is a by-product of the Phosphoric Acid factory PT Gresik Petrochemicals; it is produced around 1,200,000 tons/year. In order to reduce the amount, an effort needed to use gypsum as fill materials. For this purpose, the problem needs to be considered is that gypsum should not contain substances that harmful to the environment and meet the fill materials requirements. In order to answer all these questions, chemical tests were carried out to determine its heavy metal content. Gypsum plasticity and its particle size distribution were determined by conducting Atterberg limit and sieve analysis tests. Compaction test and CBR test were also carried out to determine the density and its strength. Those results were then analyzed using "The Fifteen Point Method" to obtain a relationship curve between dry density (d) and soaked-CBR. This curve was important to determine the soaked-CBR that can be achieved by gypsum materials in the field with different compaction energy 90%, 95%, and 100% of maximum compaction energy. Chemical test result shows that all heavy metals content in gypsum material are far below the regulatory limit; therefore, it is safe for the environment. Besides, Gypsum is non-plastic (NP) material and it is classified as A-4 (AASHTO) or SM (USCS); it means that Gypsum is very good for fill materials and safe to the environment. In addition, the result from the Fifteen Point Method shows that the minimum soaked CBR value is 13% achieved by using 90% of maximum compaction energy with 30-40 % of water content. It means that the gypsum material can be used as selected fill material because it fulfils its requirement where IP10%.